MiR-4310 regulates hepatocellular carcinoma growth and metastasis through lipid synthesis. (28th October 2021) - Li, Huayue; Chen, Zhongwu; Zhang, Yanan; Yuan, Ping; Liu, Jie; Ding, Lihua; Ye, Qinong
Abstract: Hepatocellular carcinoma (HCC), which is characterized by reprogrammed lipid metabolism, is a highly malignant tumor with a high incidence and mortality rate. While lipid metabolism is a promising target for HCC therapy, the regulation of lipid metabolism is not well elucidated. Through CRISPR/Cas9 screening, we show that miR-4310 inhibits lipid synthesis by targeting fatty acid synthase (FASN) and stearoyl-CoA desaturase-1 (SCD1). In patients with HCC, miR-4310 is significantly downregulated, and its expression is negatively correlated with expressions of FASN and SCD1. Furthermore, low expression of miR-4310 is associated with poor prognosis. By suppressing SCD1-and FASN-mediated lipid synthesis, miR-4310 inhibits HCC cell proliferation, migration, and invasion in vitro and suppresses HCC tumor growth and metastasis in vivo. Our data indicate that miR-4310 plays an important role in HCC tumor growth and metastasis by regulating the FASN- and SCD1-mediated lipid synthesis pathways. Targeting the miR-4310-FASN/SCD pathway may provide a novel strategy for HCC treatment. Highlights: MiR-4310 is negatively correlated with FASN and SCD1 in HCC patients. MiR-4310 blocks lipid synthesis via inhibiting FASN and SCD1 in HCC cells. MiR-4310 inhibits FASN and SCD1 expression by targeting their 3′-UTR. MiR-4310 represses HCC tumor growth and metastasis via inhibiting lipogenesis.